TESTING THE DYNAMIC RELATIONSHIP OF INFLATION AND INTEREST RATES: FISHER EFFECT TESTING - Setiawan, Rahmat (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This paper aims to investigate the testing of the dynamic relationship between inflation and interest rates, commonly known as the Fisher Effect, in both developed and developing countries. Testing The Fisher Effect is performed using dynamic models that include testing cointegration, testing with Error Correction Model (ECM), and testing with Autoregressive Distributed Lag (ADL). The use of dynamic models is chosen because the change of an economic variable no in a manner instantly causes the change of another economic variable at the same time, however, there is a time lag. The empirical test results show that: (1) the Fisher Effect occurs in developed countries and developing countries, both in the short term and in the long term, which means that the expected inflation affects positively the nominal interest rate in developed countries and developing countries, both in the short term and long term, (2) the determination of the nominal interest rate by commercial banks this month is influenced by inflation information in the previous month, or in other words, there is a time lag in the effect of inflation on interest rates.